Supraclavicular and Axillary Lymphadenopathy Induced by COVID-19 Vaccination on 18F-Fluorthanatrace, 68Ga-DOTATATE, and 18F-Fluciclovine PET/CT. (10th September 2021) - Surasi, Devaki Shilpa Sudha; Lin, Lilie; Ravizzini, Gregory; Wong, Franklin
Abstract: COVID-19 vaccination has started in most countries, and postvaccination imaging is inevitable in the oncologic population. The immune response to the vaccination in the form of reactive lymphadenopathy has been well documented on 18 F-FDG PET/CT. We present the imaging findings of 3 patients who have undergone non-FDG PET/CT imaging including 18 F-fluorthanatrace, 68 Ga-DOTATATE, and 18 F-fluciclovine PET/CT. It is crucial to recognize the timing and laterality of immunization to avoid false-positive findings.